Combination of AHP and SMART Methods in Determining Recipients of Direct Village Fund Cash Assistance: Kombinasi Metode AHP dan SMART pada Penentuan Penerima Bantuan Langsung Tunai Dana Desa - Nindian Puspa Dewi; Ubaidi, Ubaidi; Ismail Moadz, Ulin Najah (Digital Zone: Jurnal Teknologi Informasi dan Komunikasi, 2023)
Village Fund Direct Cash Assistance (BLT-DD) is cash assistance provided by the government to eligible residents through Village Officials whose recipients are determined based on many criteria. The process determine who is the most eligible citizen to be the recipient of BLT-DD takes a long time because of the large number of residents and the existence of several criteria used. There is a need for a decision support system that can assist village officials in choosing who is entitled to receive BLT-DD assistance. In this study, the application uses the Analytical Hierarchy Process (AHP) and Simple Multi Attributee Rating Technique (SMART) methods. The criteria used are, get assistance, income, floor area, type of floor, type of wall, and education. By using the AHP method, it is possible to optimize the weighting of the criteria and the SMART method to produce a ranking of residents who are entitled to receive BLT-DD. The results of the study indicate that this application can be used to provide recommendations to village officials in determining BLT-DD recipients.